ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI RENDAHNYA HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SD - Sinaga, Wilda Febryanti; Darwis, Umar; Dwi, Dara Fitrah; Silalahi, Beta Rapita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the internal and external factors that influence the low learning outcomes of students in the IPAS (Natural and Social Sciences) subject in Grade V at SD Negeri 104241 Kampung Syahmad Lubuk Pakam. This study uses a qualitative descriptive method. Data collection was carried out through questionnaires, interviews, and documentation. The subjects of this study were 25 Grade V students, one class teacher, and three parents of students. The results showed that internal factors, including learning interest, learning motivation, and study habits, obtained an overall percentage of 65.75%, which is categorized as very high. External factors, including the role of the teacher, learning environment, and parental support, obtained a percentage of 77.30%, also categorized as very high. The dominant internal factor affecting low learning outcomes was low learning motivation and irregular study habits, while the dominant external factor was the limited use of learning media and guidance at home. It is concluded that both internal and external factors simultaneously influence the low learning outcomes of students in the IPAS subject.